(untitled) (Hematology Meeting Reports, 2009)
There is presently a great deal of interest in linking genetic and phenotypic variation in the form of severity of, and susceptibility to, common multifactorial diseases such as sepsis. The genetic background has recently been recognized as an important element in the host response to infection, contributing to the variability in the clinical outcome of critically ill neonates. Host genetic variability in the regulatory and coding region of genes for components of innate immune system may have some bearing on the wide variability existing in the susceptibility to and outcome from sepsis even within similar neonatal intensive care unit populations. The completion of the Human Genome Project has provided insight into human genetic variation, most commonly represented by single-nucleotide polymorphisms, and has generated vast expectations. Polymorphisms in genes coding for proteins involved in the recognition of bacterial pathogens (Toll-like receptor 4, CD14) and the response to bacterial pathogens (tumor necrosis factor (TNF)-α, interleukin (IL)-1, interleukin-1 receptor antagonist (IL-1RA), IL-6, IL-10) can influence the amount or function of the protein produced in response to bacterial stimuli. Combining population genomics, bio-informatics, and clinical data may lead to the discovery of the variations that exist among the genes involved in determining susceptibility to sepsis in neonates. This review provides a background to recent advances in genetics, focusing on the application to neonatal sepsis and the practical difficulties of genetic association studies, as well as underlining the potential impact on clinical practice. Evidence is discussed suggesting that some genetic polymorphisms influence the susceptibility to and outcome from sepsis. Although still in its beginnings in neonatology, genomics will transform also this field but it will take years for the clinical implications to be revealed.